Phenotypical characteristics of severe hypertriglyceridemia - T. V. Chepetova; A. N. Meshkov; T. A. Rozhkova; P. P. Malyshev; V. V. Kukharchuk (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study clinical course and severe complication development in patients with severe hypertriglyceridemia (HTG), >10 mmol/l. Material and methods. The study included 75 patients aged 21-68 years (mean age 49±11,05 years), examined at the Cardiology Complex in 1982-2006, with verified fasting HTG >10 mmol/l. Results. Coronary heart disease (CHD) was observed in 45,2% of the participants (50% males, 37% females), arterial hypertension (AH) – in 68% (60,4% and 81,4%), Type 2 diabetes mellitus – in 42,6% (44,4% and 41,7%), pancreatitis – in 34,9% (33,3% and 37,5%, respectively). Conclusion. In patients with severe HTG, high rates of CHD, AH, metabolic syndrome and pancreatitis were observed. Therefore, to prevent severe complications in such patients, detailed examination and adequate TH and cholesterol level control are necessary.